FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN ONLINE - Dika Juliantari, Ni Kadek; Prawitasari, Putu Putri (Jurnal Bina Bangsa Ekonomika, 2025)
The purchase decision on beauty products in the Indonesian people experiences various conditions caused by changes in consumer behavior. This study aims to empirically test the factors that affect purchasing decisions on Tiktok Shop which focuses on beauty product objects including skin care, especially in the city of Denpasar. The research variables that are suspected to be able to have an impact are online customer reviews, viral marketing, and trust. This study uses a quantitative approach and data is collected using a questionnaire given to 100 people. Hypothesis testing was carried out using multiple linear regression analysis. The results of the analysis showed that online customer reviews did not have a significant effect on purchase decisions while viral marketing and trust each had a significant positive influence on purchase decisions. Simultaneously online customer reviews, viral marketing and trust have a significant positive effect on purchase decisions. So it is hoped that sellers on TikTok Shop will be able to take advantage of viral marketing methods and increase consumer confidence to be able to obtain consumer purchase decisions.